The impact of gross total resection on local control and survival in high-risk neuroblastoma - La Quaglia, Michael P; Kushner, Brian H; Su, Wendy; Heller, Glenn; Kramer, Kim; Abramson, Sara; Rosen, Nancy; Wolden, Suzanne; Cheung, Nai-Kong V (Journal of pediatric surgery, 2004)
Gross total resection of the primary tumor in treatment of high-risk neuroblastoma remains controversial. Furthermore, there are few reports of the effect of primary tumor resection on local control as opposed to overall survival. The authors reviewed their institutional experience to assess the effect of primary tumor resection on local control and overall survival. A total of 141 patients were treated on protocol between November 1, 1979 and June 25, 2002 and are the subject of this report. Gross total resection was assessed by review of operative notes, postoperative computerized axial tomograms, and postoperative meta-iodobenzyl guanidine (MIBG) 1 scans when available. The median age was 3.3 years, and all patients were International Neuroblastoma Staging System (INSS) stage 4 with 79% having metastases to cortical bone. The primary site was the adrenal gland in 74%, the central abdominal compartment in 13%, the posterior mediastinum in 7%, and other sites in 6%. Gross total resection was accomplished in 103 (73%) but was more than 90% for the last 3 protocols. Five kidneys were lost overall. The probability of local progression was 50% in unresected patients compared with 10% in patients undergoing gross total resection ( P < .01). Overall survival rate in resected patients was 50% compared with 11% in unresected patients ( P < .01). Our data indicate that local control and overall survival rate are correlated with gross total resection of the primary tumor in high-risk neuroblastoma. Gross total resection should be part of the management of stage 4 neuroblastoma in patients greater than 1 year of age.